64.4k views
4 votes
I am somewhat confused on how to do this, can someone explain? thanks!

I am somewhat confused on how to do this, can someone explain? thanks!-example-1
User TC Zhang
by
5.8k points

2 Answers

6 votes
AC = 3x - 1
AD = 12 - x
AD = AC + CD
After putting the values given above,
12 - x = 3x - 1 + CD
12 - x - 3x + 1 = CD
13 - 4x = CD

If C is the midpoint of AD then
AC = CD
3x - 1 = -4x + 13
3x + 4x = 13 + 1
7x = 14
X = 14 / 7
X = 2

CD = - 4x + 13
CD = - 4(2) + 13
CD = - 8 + 13
CD = 5
User Lidiya
by
5.0k points
5 votes

Answer:

(3x-1)×2=12-x

Explanation:

User Ddejohn
by
4.8k points